Lung transplantation for high-risk patients with idiopathic pulmonary fibrosis - De Oliveira, Nilto C; Julliard, Walker; Osaki, Satoru; Maloney, James D; Cornwell, Richard D; Sonetti, David A; Meyer, Keith C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Survival for patients with idiopathic pulmonary fibrosis (IPF) and high lung allocation score (LAS) values may be significantly reduced in comparison to those with lower LAS values. Objectives: To evaluate outcomes for high-risk IPF patients as defined by LAS values ≥46 (N=42) versus recipients with LAS values <46 (N=89). Methods: We retrospectively reviewed records of 131 consecutive patients with IPF who received lung transplants at our institution between 1999 and 2013. Results: The mean LAS was significantly higher (59.5, interquartile range 43.9-75.9 vs. 39.3, interquartile range 37.7-44.3; p<0.01) for the high-risk cohort. The higher LAS cohort had significantly lower percent predicted forced vital capacity (FVC) versus recipients with LAS <46 (41.3±14.1% vs. 53.2±16.2%; p<0.01) and required more supplemental oxygen (7±5 vs. 4±2 L/min, p<0.01) prior to transplant versus recipients with LAS <46. Although the incidence of early post-LTX pulmonary complications was increased for the higher LAS group versus recipients with LAS <46, 30-day mortality and actuarial survival did not differ between the two cohorts. Conclusions: Although lung transplantation in patients with IPF and high LAS values is associated with increased risk of early post-transplant complications, long-term post-transplant survival for our high-LAS cohort was equivalent to that for the lower LAS recipients.